(untitled) (Balthazar, 2024)
Benjamin was perhaps Kafka’s most congenial critic, and he was among the first to understand the scope and value of the challenge posed by his entire literary oeuvre. In one of his notes, written in the 1930s, Benjamin placed Baudelaire and Kafka side by side, pointing to the former as a key figure in the literature of the xix century and the latter as that of the xxcentury. The article seeks to show how the main themes of Benjamin’s thought find the ground for elaboration and unraveling in the confrontation with Kafka’s work, opening up a perspective that interweaves the force of criticism with the sometimes visionary view of the most current aesthetic tensions.